Detecting Academic Difficulties (Reading, Writing, Arithmetic) Among First-Year Middle School Pupils from the Teachers' Perspective - عابي صفية; عنيبي ياسمينة; اشراف:جلاب مصباح (جامعة محمد بوضياف المسيلة, 2024)
This study aimed to uncover learning difficulties among first-year middle school pupils from the perspective of teachers, considering it a crucial stage in their educational journey. To narrow down the scope of this exploratory study, we attempt to answer the following question: Do first-year middle school pupils experience learning difficulties (reading, writing, arithmetic) from the teachers' perspective? Through a field study in which a questionnaire was applied to a sample of 75 teachers from Al-Ma'adid Middle School in M'sila, selected purposefully, the study aimed to answer the initial question. The following results were recorded: -the overall arithmetic mean for the first axis (reading difficulties) reached 1.720, with a standard deviation of 0.138, indicating a high degree. This implies that students are facing reading difficulties from the perspective of their teachers. -the overall arithmetic mean for the second axis (writing difficulties) was 1.66, with a standard deviation of 0.197, indicating a moderate degree. This implies that students are facing moderate writing difficulties. -the overall arithmetic mean for the third axis (mathematics difficulties) was 1.833, with a standard deviation of 0.109, indicating a high degree. -the overall arithmetic mean for the survey was 1.738, with a standard deviation of 0.131, indicating a high degree. This indicates that teachers perceive first-year middle school students to experience academic learning difficulties (reading, writing, arithmetic) to a high extent. القواعد الفقهية، الإذن الشرعي، الضمان، الإتلاف. الكلمات المفتاحية